Asymptomatic Bacteriuria among Pregnant Women Attending Tertiary Care Hospital in Lucknow, India - Naimshree Sonkar; Malay Banerjee; Suman Gupta; Absar Ahmad (Dubai Medical Journal)
Introduction: Asymptomatic bacteriuria (ASB) is the presence of actively multiplying bacteria within the urinary tract with absence of any symptoms, resulting in adverse pregnancy outcomes. This research study was done in order to review prevalence, antimicrobial susceptibility profile, and factors associated with ASB occurring in female patients who are pregnant and being treated at a tertiary care hospital in Lucknow, India. Method and Materials: This is a cross-sectional study done among 216 pregnant women attending a hospital for antenatal check-ups. Clean catch midstream urine samples were collected and examined microscopically, and semi-quantitative culture was done on blood agar and MacConkey agar. Isolates were identified by colony morphology and biochemical tests, and antimicrobial susceptibility testing was done by using the Kirby-Bauer method. Results: Of the 216 pregnant women, 36 (16.7%) tested positive for ASB. The female gestational period, haemoglobin level, and BMI were significantly associated with ASB. Logistic regression also showed that higher haemoglobin level was less likely to ASB (AOR = 0.42, 95% confidence interval: 0.202–0.88, p = 0.021). The predominant and usual isolates were E. coli (n = 22, 61.1%), followed by Cons (n = 6, 16.7%), and S. aureus (3, 8.3%). All Gram-negative isolates were mostly sensitive to most of the drugs like piperacillin-tazobactam, cefepime, nitrofurantoin, and meropenem but were 100% resistant to ampicillin. Similarly, Gram-positive isolates were sensitive to ampicillin, vancomycin, linezolid, and nitrofurantoin but 100% resistant to co-trimoxazole. Conclusion: The present study shows the existence of ASB was 16.7% among women who are pregnant. Pregnancy duration, haemoglobin level, and BMI were significantly associated with ASB. The isolates identified more frequently were E. coli (61.16%), Cons (16.7%), and S. aureus (8.3%). All isolates which were Gram-negative were mostly sensitive to most of the drugs but were 100% resistant to ampicillin. Similarly, Gram-positive isolates were sensitive to most of the drugs but 100% resistant to co-trimoxazole.